Governance Capacity in Efforts to Reduce Stunting in West Java - Maulana Yusup, Rikki; Fitriyani, Zeilin; Rahardian, Ramaditya (Iapa Proceedings Conference, 2024)
The problem of stunting is still a serious challenge in Indonesia, which is ranked fifth globally in stunting prevalence according to UNICEF. Stunting, which is determined based on a child's height according to age, has a significant impact on children's health and development, including decreased cognitive function. This study attempts to analyze governance capacity in overcoming stunting in West Java. This study uses a descriptive qualitative approach to explore the role of the government in managing stunting in West Java. This qualitative method aims to understand social meaning through interviews with informants from the Health Office, Duta Genre, and the Regional Planning Agency. Interactive analysis is used in data analysis, as well as for data validity using triangulation of sources and techniques. The results of the study show that the Acceleration of Stunting Reduction (TPPS) of the West Java Province is tasked with coordinating, synergizing, and evaluating efforts to reduce stunting through cross-sector collaboration. At the Regency/City level, TPPS integrates regional apparatus and stakeholders, including TP-PKK. To support the program, the organizational structure involves various agencies, including BAPPEDA and the Health Office, as well as NGO. The regulations underlying this program include the Presidential Regulation on the Acceleration of Stunting Reduction, with a focus on preventing stunting before and after birth. Counseling the community about stunting is very important to increase awareness. Finally, Implementation is carried out with a holistic approach, including specific and sensitive interventions, as well as periodic monitoring to achieve the target of reducing the prevalence of stunting that has been set.